2010
DOI: 10.1080/09658211.2010.509731
|View full text |Cite
|
Sign up to set email alerts
|

Imagery encoding and false recognition errors: Examining the role of imagery process and imagery content on source misattributions

Abstract: Imagery encoding effects on source-monitoring errors were explored using the Deese-Roediger-McDermott paradigm in two experiments. While viewing thematically related lists embedded in mixed picture/word presentations, participants were asked to generate images of objects or words (Experiment 1) or to simply name the items (Experiment 2). An encoding task intended to induce spontaneous images served as a control for the explicit imagery instruction conditions (Experiment 1). On the picture/word source-monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 78 publications
0
13
0
1
Order By: Relevance
“…Unlike memory for actions (Thomas et al 2003), there was not an inflation of memory errors following more elaborate encoding for BE. We also found no reduction of BE, as had been observed for imagined objects (Foley et al 2010), suggesting that memory was not improved by the act of imagining additional details.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Unlike memory for actions (Thomas et al 2003), there was not an inflation of memory errors following more elaborate encoding for BE. We also found no reduction of BE, as had been observed for imagined objects (Foley et al 2010), suggesting that memory was not improved by the act of imagining additional details.…”
Section: Discussionmentioning
confidence: 56%
“…Regardless of whether we asked them to imagine additional sounds, odors, tastes, or even visually what more of the photograph would look like, elaboration did not increase BE. Elaboration also did not reduce BE, which might have occurred if the act of generating additional information improved accuracy, as Foley et al (2010) had found within the Deese/Roediger-McDermott paradigm for word and picture lists.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations